2019
DOI: 10.1016/j.compfluid.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Conservative and adaptive level-set method for the simulation of two-fluid flows

Abstract: In this paper, we present a high fidelity conservative and adaptive level-set method for the simulation of two-fluid flows. A new level-set method is designed that associates both re-initialization and convection steps in an implicit manner. Thus the new obtained convection-reaction problem is solved using a stabilized finite element method. The accuracy, the time scheme and the mass conservation are thoroughly analyzed. Anisotropic meshing with conservative interpolation is implemented and tested on several b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…We propose in this work an adaptive Eulerian framework for the simulation of both boiling and evaporation phenomena occurring at the interface of a heated 3D solid immersed in a liquid tank. It was shown that an adaptive Eulerian framework is very efficient for the simulation multiphase flows [25][26][27][28], compressible and incompressible flows [29] and yield stress fluids [30]. This framework takes into account the gas-liquid phase changes, the vapor formation and their dynamics, and enables consequently the simulation of 3D quenching or cooling of a heated solid.…”
Section: Introductionmentioning
confidence: 99%
“…We propose in this work an adaptive Eulerian framework for the simulation of both boiling and evaporation phenomena occurring at the interface of a heated 3D solid immersed in a liquid tank. It was shown that an adaptive Eulerian framework is very efficient for the simulation multiphase flows [25][26][27][28], compressible and incompressible flows [29] and yield stress fluids [30]. This framework takes into account the gas-liquid phase changes, the vapor formation and their dynamics, and enables consequently the simulation of 3D quenching or cooling of a heated solid.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this auto-reinitialization transport equation ( 43) is solved in finite-element by means of Streamline Upwind PetrovGalerkin (SUPG) method known to mitigate the numerical instabilities. See [24] for more numerical details.…”
Section: Level-set Methodsmentioning
confidence: 99%
“…As for the numerical flux of (u h ′ ϕ h ′ ) * , we choose the Lax-Friedrichs flux in equation (17) to substitute it:…”
Section: Solver For Level Set and Its Reinitialization Equationsmentioning
confidence: 99%
“…e same order interpolation functions are used for the velocity and pressure. As for the capturing of free surface, the simple and efficient level set method [16,17] is utilized. We employ the implicit discontinuous Galerkin method [18,19] to handle the level set and its reinitialization equations for the accuracy and stability.…”
Section: Introductionmentioning
confidence: 99%